On the Slowly Decreasing Sequences of Fuzzy Numbers - Özer Talo; Feyzi Başar (Abstract and Applied Analysis)
We introduce the slowly decreasing condition for sequences of fuzzy numbers. We prove that this is a Tauberian condition for the statistical convergence and the Cesáro convergence of a sequence of fuzzy numbers.